Análise numérica dos esforços eletromecânicos nos enrolamentos de transformadores de portência sob curto-circuito - Cornelius, Richard Gonçalves (2023)
Power transformers are devices present in the connections of transmission lines and substations, they are essential for the transmission and distribution of electrical energy due to their ability to adapt voltage and current levels. Due to these aspects, there are several concerns about problems that may compromise its correct functioning, or even remove it from operation, which could interrupt the continuous power supply. One of these events are short circuits, which impose large electrical, thermal and mechanical demands on the electrical network and the equipment that compose it. During this transient fault, the transformers are disposed to high electromechanical forces that can cause deformations in their windings and, consequently, their failure. This work presents a methodology for determination of electromechanical forces and their distribution in the windings of power transformers through simulations using the Finite Element Method. For this, physical concepts about electromagnetic forces and how they manifest in transformer windings are addressed, concepts about mechanical stresses and properties of materials used in coil manufacturing are also presented. Moreover, the deformations types that can occur in the windings and resulting damages are highlighted. Then, the Waters analytical method for the determination of electromagnetic forces is approached, highlighting its premises and considerations for performing the calculations. In addition, analytical methods are presented for the determination of mechanical stresses arising from electromagnetic forces, where the analyzes are applied to stresses that cause buckling and bending deformations. Then, the methodology proposed by this work is presented and three 3D coil arrangements are modeled: coils of same height without tap, tap on the headboard and tap on the middle. Therefore, the results of the finite element simulations are compared with the results obtained analytically in order to validate the method. Then, electromagnetic forces and mechanical stresses on divisions modeled along the winding discs are detailed, identifying the behavior of these quantities and critical points affected by them. In general, the methodology proved to be efficient, and able to assist in the projects of mechanical support of transformers.